Saya Keras Demi Kepentingan Peserta Didik! Refleksi Pendidik terhadap Prinsip Mengajar dan Profesinya - Kamarullah Kamarullah; Barep Sarinauli (IAIN Takengon, 2023)
Teachers are ‘actors’ who have many roles in education. Internal and external conditions are often not exposed by this profession. This study explores the issue of principles and the teaching profession as material for their reflection. Qualitatively, the researcher compiled the data from interviews with three selected informants to present their perspectives on the two issues mentioned. The data obtained were analyzed by being narrowed, displayed, and drawn conclusions. The findings show that educators have their teaching principles in motivating themselves and students. They are committed to carrying out their profession regardless of the educational dynamics.